2008
DOI: 10.1121/1.2896962
|View full text |Cite
|
Sign up to set email alerts
|

Human listeners attend to size information in domestic dog growls

Abstract: Vocal expressions of emotions follow simple rules to encode the inner state of the caller into acoustic parameters, not just within species, but also in cross-species communication. Humans use these structural rules to attribute emotions to dog vocalizations, especially to barks, which match with their contexts. In contrast, humans were found to be unable to differentiate between playful and threatening growls, probably because single growls' aggression level was assessed based on acoustic size cues. To resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 40 publications
6
60
1
Order By: Relevance
“…As formant dispersion is controlled by VTL, this means that unlike F0, formants have the potential to provide accurate or 'honest' information about the caller (Fitch, 1997;Reby & McComb, 2003). A direct negative correlation between formant dispersion and body size has been confirmed in the signals of many species, including dog growls (Riede & Fitch, 1999;Taylor et al, 2008). When we analyse formant dispersion within any growl, it is thus possible to predict the body size of the caller.…”
Section: Indexical Informationmentioning
confidence: 99%
See 4 more Smart Citations
“…As formant dispersion is controlled by VTL, this means that unlike F0, formants have the potential to provide accurate or 'honest' information about the caller (Fitch, 1997;Reby & McComb, 2003). A direct negative correlation between formant dispersion and body size has been confirmed in the signals of many species, including dog growls (Riede & Fitch, 1999;Taylor et al, 2008). When we analyse formant dispersion within any growl, it is thus possible to predict the body size of the caller.…”
Section: Indexical Informationmentioning
confidence: 99%
“…Within dog breeds, those of comparable size to wolves show similar levels of body mass dimorphism, which was found to relate to a difference of 5%-7% in vocal tract length (VTL) between adult males and females for Portuguese water dogs (Plotsky et al, 2013). However, the size difference between sexes decreases in smaller breeds (Frynta et al, 2012), and no sex-related differences in vocal anatomy or in F0 have been identified across breeds when controlling for body weight (Riede & Fitch, 1999;Taylor et al, 2008). However, artificial selection by humans has led to an exceptionally large level of size variation between breeds, giving dogs the highest level of morphological variation of any mammal (Wayne, 1993).…”
Section: Indexical Informationmentioning
confidence: 99%
See 3 more Smart Citations